Investigating the Causal Effect of Brain Expression of CCL2, NFKB1, MAPK14, TNFRSF1A, CXCL10 Genes on Multiple Sclerosis: A Two-Sample Mendelian Randomization Approach - Fazia, Teresa; Nova, Andrea; Gentilini, Davide; Beecham, Ashley; Piras, Marialuisa; Saddi, Valeria; Ticca, Anna; Bitti, Pierpaolo; McCauley, Jacob L.; Berzuini, Carlo; Bernardinelli, Luisa (Frontiers in Bioengineering and Biotechnology, 2020)
Multiple Sclerosis (MS) exhibits considerable heterogeneity in phenotypic expression, course, prognosis and response to therapy. This suggests this disease involves multiple, as yet poorly understood, causal mechanisms. In this work we assessed the possible causal link between gene expression level of five selected genes related to the pro-inflammatory NF-κB signalling pathway (i.e., CCL2, NFKB1, MAPK14, TNFRSF1A, CXCL10) in ten different brain tissues (i.e., cerebellum, frontal cortex, hippocampus, medulla, occipital cortex, putamen, substantia nigra, thalamus, temporal cortex and intralobular white matter) and MS. We adopted a two-stage Mendelian Randomization (MR) approach for the estimation of the causal effects of interest, based on summary-level data from 20 multiplex Sardinian families and data provided by the UK Brain Expression Consortium (UKBEC). Through Radial-MR and Cochrane’s Q statistics we identified and removed genetic variants which are most likely to be invalid instruments. To estimate the total causal effect, univariable MR was carried out separately for each gene and brain region. We used Inverse-Variance Weighted estimator (IVW) as main analysis and MR-Egger Regression estimator (MR-ER) and Weighted Median Estimator (WME) as sensitivity analysis. As these genes belong to the same pathway and thus they can be closely related, we also estimated their direct causal effects by applying IVW and MR-ER within a multivariable MR (MVMR) approach using set of genetic instruments specific and common (composite) to each multiple exposures represented by the expression of the candidate genes. Univariate MR analysis showed a significant positive total causal effect for CCL2 and NFKB1 respectively in medulla and cerebellum. MVMR showed a direct positive causal effect for NFKB1 and TNFRSF1A, and a direct negative causal effect for CCL2 in cerebellum; while in medulla we observed a direct positive causal effect for CCL2. Since in general we observed a different magnitude for the gene specific causal effect we hypothesize that in cerebellum and medulla the effect of each gene expression is direct but also mediated by the others. These results confirm the importance of the involvement of NF-κB signalling pathway in brain tissue for the development of the disease and improve our understanding in the pathogenesis of MS.